Peran Komisi Kejaksaan Dalam Mengawasi Kinerja Kejaksaan Sebagai Pelaksana Asas Dominus Litis Dalam Penyelesaian Perkara Korupsi - Kalalo, Gabriel; Tjoneng, Arman (Universitas Ekasakti, 2024)
The dominus litis principle is a principle that gives authority to the public prosecutor to control criminal cases. This principle confirms that no other body has the right to carry out prosecutions other than the public prosecutor. In the legal system in Indonesia, the principle of dominus litis is confirmed in Article 1 number 25 of Law Number 16 of 2004 concerning the Prosecutor's of the Republic of Indonesia. This article states that a public prosecutor is an official who is authorized by law to act as a public prosecutor in criminal cases, especially corruption cases. Then, legal problems that arise in the field still include the practice of bribery with the aim of mitigating or even acquitting through P3 letters, fatwa issuance scandals, and exceptions to indictments to reduce sentences, so enforcement and supervision are needed to overcome this. The research uses a Normative Juridical research method and uses a Statute Approach and a Case Approach, where this research focuses on legal principles, statutory regulations, legal rules and cases related to this research. With the existence of the dominus litis principle, it is hoped that the criminal law enforcement process in Indonesia can run more effectively and efficiently. Discussion regarding law enforcement and the role of the prosecutor's commission is an urgency considering that prosecutors as pioneers are expected to be in line with practice in the field, so that in the future the prosecutor's office as the holder of the Dominus Litis principle does not happen again which makes a prosecutor get involved in handling a corruption case.